FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KEHAMILAN TIDAK DIINGINKAN PADA REMAJA DI WILAYAH KECAMATAN BOLANGITANG BARAT - Ani Retni; Fahmi A. Lihu (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
From the data obtained in pregnancy health center and health center Olot West Bolangitang showed that pregnant teenagers in 2014 amounted to 44 people. Pregnancy teenagers in the District of West Bolangitang after confirmed by the health center because of several factors such as sex outside marriage, given the lack of parental guidance, lack of knowledge about adolescent sex can lead to pregnancy, teens having sex without using contraception, rape, environmental factors association with the presence of friends and habits and addictive to watch pornographic films. The problems of the study are: What Factors Associated With Occurrence of Unwanted Pregnancy In Teenagers on the District of West Bolangitang?. Objective study the factors associated with the occurrence of unintended pregnancy in adolescents in the District of West Bolangitang. The design study is a descriptive analytic study with cross sectional approach. Results and discussion of research suggests that (a) Of the 30 sampled adolescents who have sex less knowledge which amounted to 28 people and who has a good knowledge of sex amounted to 2 people, while the incidence of pregnancy due to rape and incest does not occur in the study subjects. Adolescents who experience unintended pregnancies events totaled 29 respondents who experienced an unwanted pregnancy and first responders who have unwanted pregnancies. (b) In general, adolescents experiencing an unwanted pregnancy have less knowledge. (c) Knowledge of sex associated with unintended pregnancy in adolescents in the District of West Bolangitang indicated by the chi-square value = 0.000 while the table for α = 0.05 level with df = 1 for 3,841. (d) The rape and pregnancy due to incest in a constant state of not dealing with an unwanted pregnancy in adolescents in the District of West Bolangitang.